1983
DOI: 10.2355/isijinternational1966.23.169
|View full text |Cite
|
Sign up to set email alerts
|

Fluid flow and mixing characteristics in a gas-stirred molten metal bath.

Abstract: SynopsisFluid flow and mixing characteristics in a molten metal bath are analyzed for inert gas injection through a nozzle at the center of the vessel bottom. It is postulated that the bath consists of two zones; bubble plume zone where gas-liquid mixtures flow upward and annular zone where liquid flows downward. The analysis is made by setting up a steady-state energy balance for the liquid phase. The liquid velocity in the plume zone, the liquid circulating flow rate and the mixing time are calculated for va… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
37
0
5

Year Published

1984
1984
2016
2016

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 63 publications
(43 citation statements)
references
References 0 publications
1
37
0
5
Order By: Relevance
“…Nowadays it is generally accepted that the power of " is dependent on the mode of energy input and the vessel geometry. 5,12,[19][20][21][22] The same functional relationship as derived by Nakanishi et al 1) was valid for the presently measured values, as shown in Fig. 12 …”
Section: Effect Of Gas Flow Rate On Mixing Timesupporting
confidence: 52%
“…Nowadays it is generally accepted that the power of " is dependent on the mode of energy input and the vessel geometry. 5,12,[19][20][21][22] The same functional relationship as derived by Nakanishi et al 1) was valid for the presently measured values, as shown in Fig. 12 …”
Section: Effect Of Gas Flow Rate On Mixing Timesupporting
confidence: 52%
“…The energy balance applicable to gas stirred ladle system as invoked by Sahai and Guthrie 8) as well as Sano and Mori 13) was based on the assumption that the rate at which energy is imparted by the rising bubbles is balanced under steady state conditions by the rate at which turbulence kinetic energy is dissipated within the system. However, because of bubble slippage, waves and droplet formation at the free surface as well as friction at the wall, it is unlikely that turbulence phenomena alone would dissipate all of the supplied input energy to the system.…”
Section: )mentioning
confidence: 99%
“…This, together with many other characteristics of the gas stirred ladle systems, has accordingly been applied as a basis in many subsequent studies on hydrodynamics, mixing etc. [8][9][10][11][12][13][14] Considerable efforts have been made by various group of researchers to develop expressions to show how plume rise velocity (i.e., average rise velocity of the two phase gas liquid mixture) and average speed of liquid recirculation within the vessel can be predicted ab initio in terms of the key ladle operating variable such as, gas flow rates, and vessel dimension. Thus, Sahai and Gutrhrie 8) were among the first to develop and propose an explicit correlation between plume rise velocity and the operating parameters.…”
Section: Macroscopic Process Modelsmentioning
confidence: 99%
“…In a series of recent contributions,1~3) Krishnamurthy and coworkers have investigated mixing phenomena in gas stirred liquid baths and have proposed a modelbased on the concept of a "circulation time. "I' 4,5) Their modell) in its updated form2) was used to assess our experimental studies of mixing, which reported on 10cation effects of tracer addition and monitoring poipts on mixing times.6~9) To illustrate this, a sample comparison between Krishnamurthy's calculated results3) and previous experimental data by ourselves,6) reproduced from ref. 3, is shown in Fig.…”
Section: Introductionmentioning
confidence: 99%